Caveolin-1 in vascular health and glaucoma: A critical vascular regulator and potential therapeutic target - Loo, Jing Hong; Wang, Zhaoran; Chong, Rachel S. (Frontiers in Medicine, 2023)
Caveolin-1 (Cav-1) is an integral scaffolding membrane protein found in most cell types. Cav-1 has been found to contribute significantly to ocular function, with mutations of Cav-1 being associated with a genetic risk of glaucoma development. Raised intraocular pressure (IOP) is a major modifiable risk factor for glaucoma. Cav-1 may be involved in both IOP-dependent and independent mechanisms involving vascular dysregulation. Systemic vascular diseases including hypertension, diabetes and hyperlipidaemia, have been shown to be associated with glaucoma development. Cav-1 is closely interlinked with endothelial nitric oxide synthase pathways that mediate vascular function and prevent cardiovascular diseases. Endothelial nitric oxide synthase and endothelin-1 are key vasoactive molecules expressed in retinal blood vessels that function to autoregulate ocular blood flow (OBF). Disruptions in the homeostasis of OBF have led to a growing concept of impaired neurovascular coupling in glaucoma. The imbalance between perfusion and neuronal stimulation arising from Cav-1 depletion may result in relative ischemia of the optic nerve head and glaucomatous injury. OBF is also governed by circadian variation in IOP and systemic blood pressure (BP). Cav-1 has been shown to influence central BP variability and other circadian rhythms such as the diurnal phagolysosomal digestion of photoreceptor fragments and toxic substrates to maintain ocular health. Overall, the vast implications of Cav-1 on various ocular mechanisms leading to glaucoma suggest a potential for new therapeutics to enhance Cav-1 expression, which has seen success in other neurodegenerative diseases.